UPAYA MENINGKATKAN HAFALAN PERKALIAN MATEMATIKA DENGAN MENGGUNAKAN METODE BERNYANYI PADA SISWA KELAS 2 SD DI MUHAMMADIYAH 12 PAMULANG BANTEN - Zulfitria Zulfitria (Universitas Muhammadiyah Jakarta, 2019)
Mathematics is one of the most frightening learning for students, the real ability of social teaching is low. One way to improve students' multiplication skills by memorizing multiplication using the singing method.Research to find out how to learn mathematics in multiplication learning through memorizing methods by singing at Muhammadiyah Elementary School 12 Pamulang-Banten. The subject of the study was the second grade students of Al-Farisi class from August to September 2018.The research results obtained from each cycle have expressions from each cycle. This can be done by using the method of memorizing multiplication more pleasant and making it easier for students to remember it. Student students learn the assignments given by the teacher.